Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.jvs.2016.03.422
|View full text |Cite
|
Sign up to set email alerts
|

Readmission rates after lower extremity bypass vary significantly by surgical indication

Abstract: The 30-day readmission rates after lower extremity bypass vary significantly by surgical indication. Because lower extremity bypasses are performed for multiple indications, if readmission rates are publically reported and hospitals can be penalized for higher than expected readmission rates, the expected readmission rates should be adjusted for surgical indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 18 publications
(25 reference statements)
1
27
0
Order By: Relevance
“…Lower-extremity bypass procedures are associated with a high rate of unplanned re-admissions [4,10]. We found that among patients re-admitted with an infection, surgical site infection and LE cellulitis were the most common.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Lower-extremity bypass procedures are associated with a high rate of unplanned re-admissions [4,10]. We found that among patients re-admitted with an infection, surgical site infection and LE cellulitis were the most common.…”
Section: Discussionmentioning
confidence: 84%
“…Co-morbidities associated with re-admission and infection in bivariable analysis included a diagnosis of diabetes at the time of the index procedure. Previous investigations have supported this conclusion indirectly by demonstrating a direct association between insulindependent diabetes and a higher risk of 30-d re-admission [4,12,22]. Although the association between diabetes and re-admission is not surprising, it may well represent an association between poor glucose control and an overall higher risk of infection.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…6,7 Specifically, vascular surgery patients are known to have high postoperative readmission rates, regardless of the procedure. [8][9][10][11][12][13][14][15][16][17][18][19] This circumstance is particularly true for patients undergoing lower extremity infrainguinal bypass (LEB). [10][11][12][13][14][15] Readmission data identified in previous studies only considered postoperative readmission at 30 days and have been high, ranging from 14% to 24%.…”
mentioning
confidence: 99%
“…Furthermore, rising costs and an increased inpatient readmission rate are often consequences of diabetes mellitus [5,22,23]. As published by the International Diabetes Federation (IDF), Germany ranks third among the top 10 countries worldwide in terms of costs and expenses caused by diabetes mellitus in adults (20-79 years) [1,24].…”
Section: Diabetes Mellitusmentioning
confidence: 99%